Analysis of the mechanism of energy consumption for CO2 capture in a power system. (1st January 2023) - Zheng, Yawen; Gao, Lin; He, Song
Abstract: The rather high energy penalty of CO2 capture is the critical gap deterring the deployment of Carbon capture and storage technologies. A deeper understanding of the mechanism of CO2 capture will lay a foundation for reducing energy consumption. Accordingly, this paper introduced a thermodynamic analysis method with a new criterion to reveal the mechanism of energy consumption in a power system integrating CO2 capture. The results indicate that although the energy consumption of the separation process in post-combustion capture is generally recognized as the dominant part of the capture penalty, the deterioration of energy utilization in power systems due to the provision of energy for CO2 separation is nonnegligible. For an improvement in separation efficiency, the ceiling of 50% separation efficiency indicates a penalty as low as 6 percent points, and a CO2 capture cost of approximately 24 $/tCO2 can be anticipated. For system integration, improving the energy-supplying method by shifting to an external energy source may be expected to be a preferable way to save energy. With the aid of the new thermodynamic analysis method, a better understanding of the performance of diverse CO2 capture technical routes can be obtained, which may be helpful for reducing energy consumption in CO2 capture technologies. Highlights: A thermodynamic analysis method with a new criterion was introduced. The internal mechanism of CO2 capture energy consumption was revealed. Better understand of diverse CO2 capture technical routes can be obtained. 50% separation efficiency indicates 6 points penalty for CO2 capture system. CO2 capture cost of about 24 $/t CO2 can be expected for 50% separation efficiency.